Real-world performance and utility of a noninvasive gene expression assay to evaluate melanoma risk in pigmented lesions. Issue 5 (October 2018) - Ferris, Laura K.; Gerami, Pedram; Skelsey, Maral K.; Peck, Gary; Hren, Catherine; Gorman, Christopher; Frumento, Tana; Siegel, Daniel M.
Abstract : About 3 million surgical pigmented skin lesion biopsies are performed each year in the USA alone to diagnose fewer than 200 000 new cases of invasive melanoma and melanoma in situ using the current standard of care that includes visual assessment and histopathology. A recently described noninvasive adhesive patch-based gene expression rule-out test [pigmented lesion assay (PLA)] may be helpful in identifying high-risk pigmented skin lesions to aid with surgical biopsy decisions. The main objective of this utility study was to determine the real-world clinical performance of PLA use and assess how the PLA changes physician behavior in an observational cohort analysis of 381 patients assessed with the PLA. All (100%) of 51 PLA(+) test results were clinically managed with surgical biopsy. Of these, 19 (37%) were melanomas, corresponding to a number needed to biopsy of 2.7 and a biopsy ratio of 1.7. All melanomas were histopathologically classified as melanoma in situ or stage 1. Nearly all (99%) of 330 PLA(−) test results were clinically managed with surveillance. None of the three follow-up biopsies performed in the following 3–6 months, were diagnosed as melanoma histopathologically. The estimated sensitivity and specificity of the PLA from these data sets are 95 and 91%, respectively. Overall, 93% of PLA results positive for both LINC00518 and PRAME were diagnosed histopathologically as melanoma. PRAME -only and LINC00518-only lesions were melanomas histopathologically in 50 and 7%, respectively. The PLA alters clinical management of pigmented lesions and shows high clinical performance. The likelihood of positive histopathologic diagnosis of melanoma is higher in PLA results that are positive for both LINC00518 and PRAME .